Pentraxins as Key Disease Markers for Periodontal Diagnosis. Issue 3 (21st May 2013) - Kathariya, Rahul; Jain, Hansa; Gujar, Dnyneshwari; Singh, Archana; Ajwani, Himanshu; Mandhyan, Devendra
Abstract : Periodontal diseases are characterized by a complex set of biologic interactions between a diverse and dynamic microbial ecosystem and the host's multifaceted and responsive immune and inflammatory machinery. Such interactions between microbial pathogens and various host response systems play a critical role in the development and progression of periodontal disease via the release of inflammatory and immune mediators. Advances in periodontal disease diagnostic are moving toward methods whereby periodontal risk can be identified and quantified by detecting such inflammatory mediators in its sequential pathophysiology. Pentraxins (PTXs) are classical mediators of inflammation and markers of acute-phase reaction. They are a super family of multifunctional molecules characterized by multimeric structure, divided into "short" PTXs and "long" PTXs. C-reactive protein (CRP) and pentraxin-3 (PTX3) are prototypic molecules of the short and long PTX family, respectively. Evidence suggests that PTXs acts as a non-redundant component of the humoral arm of innate immunity, downstream of, and complementary to, cellular recognition, as well as a tuner of inflammation. CRP is a cheaper biomarker and more readily available in everyday clinical practice compared with other inflammatory markers, on the other hand, PTX3 is believed to be the true independent indicator of disease activity and could have clinical implication in diagnosing the "at site" inflammatory status of the periodontal disease. These pentraxins are sensitive and specific in the diagnosis and prognosis of chronic diseases. Thus the pentraxins could be used as preferred biomarkers in periodontal disease diagnosis.